The color of plant reproduction: macroecological trade-offs between biotic signaling and abiotic tolerance - Burns, Kevin C. (Frontiers in Ecology and Evolution, 2015)
Flowers and fruits are often vividly coloured. An obvious explanation for fruit and flower pigmentation is that it serves to attract animal mutualists. However, decades of research has produced surprising little support for this hypothesis. Exciting new research into geographic variation in flower colours suggests an alternative explanation - flower pigments protect gametes against the damaging effects of solar radiation. Here, I present several new analyses suggesting that a similar explanation might apply to Rubus spectabilis, a much studied but poorly understood bird-dispersed fruit species. These and other recent results provide a new perspective on the colour of plant reproduction. In addition to signalling to animals, fruit and flower colours might often play vital roles in protecting plants against the harmful effects of solar radiation.